Understanding the consumers’ multi-competing brand community engagement: A mix method approach - He, Kai; Liao, Junyun; Li, Fengyan; Sun, Hongguang (Frontiers in Psychology, 2023)
It is increasingly common for consumers to participate in multiple competing brand communities simultaneously, which brings challenges for companies to manage brand communities and build strong brand-consumer relationships. Previous studies on brand communities mainly focus on consumers’ engagement in an individual community, neglecting consumers’ behavior of multi-competing brand community engagement (MBCE). To fill this research gap, this paper explores the manifestation and categories of consumers' MBCE through two studies using two different methodologies. By employing netnography, study 1 shows that MBCE behaviors can be classified into three categories: information-oriented MBCE, social-oriented MBCE, and oppositional MBCE. Through a consumer survey, Study 2 indicates that one reason that motivates consumers to participate in other competing brand communities is because of the attractiveness of other competing brands. Also, the results indicate that consumers’ product knowledge is positively associate with MBCE. Finally, the number of competing brand community engagement is positively related to brand switching intention. This article enriches the brand community literature and provides important implications on managing brand communities in a competing environment.